Scent of the missing : love and partnership with a search-and-rescue dog - Charleson, Susannah (Houghton Mifflin Harcourt, 2010)
After the Oklahoma City bombing in 1995, Susannah Charleson was so impressed by the newspaper photo of an exhausted handler and his search-and-rescue dog that she decided to train a dog of her own. A dog lover and pilot with search experience herself, Charleson got Puzzle, a strong, bright Golden Retriever, who from the start, exhibited a unique aptitude for search-and-rescue work. But the puppy's willfulness challenged even Susannah, who had raised dogs for years. Scent of the Missing is the story of Susannah and Puzzle's adventures and the complex relationship they forge as they help in the pursuit and recovery of people who have fallen prey to crime, misadventure, or catastrophe.